Clinicodemographic Profile of Childhood Cancer in a Mining State, Odisha: A Retrospective Analysis - Samanta, Dipti Rani; Avinash, Ajitesh; Senapati, Surendra Nath; Samal, Suchitra; Dash, Tapas Kumar; Sarangi, Abhisekh Kumar (Indian Journal of Medical and Paediatric Oncology, 2023)
Introduction Pediatric malignancy represents 5% of total cancer diagnosed in India. Due to delayed diagnosis and inaccessibility to healthcare system, the overall outcome is poor in our country. The clinicodemographic profile of childhood malignancy is well described in the Western world and in certain parts of India. The incidence of pediatric malignancy in Eastern India, especially Odisha, has not yet been reported that has motivated us to conduct such a study.Objective This study aims to evaluate the clinicodemographic profile and pattern of childhood malignancy among pediatric patients who received the treatment at a tertiary cancer institute of Odisha.Materials and Methods It was a retrospective observational study, carried out for a period of 8 years, from January 1, 2013 to December 31, 2020 at a tertiary cancer center in Eastern India. A total of 759 eligible childhood malignancy patients were recruited in the study. IBM SPSS v23 was used for descriptive statistical analysis, that is, number and percentage of various clinicodemographic parameters of the above patients.Result Childhood malignancy accounted for 1.6% of all cancers reported during the above study period. The male to female ratio was 1.8:1. Out of 759 eligible childhood cancer patients, majority of patients were suffering from leukemia (173; 22.8%) followed by malignant bone tumors (137; 18.0%), and lymphoma (122; 16%). Leukemia was predominant in the age group of 0 to 14 years; lymphoma, central nervous system neoplasms, germ cell tumors malignant bone tumors, and soft tissue sarcoma (STS) were common in the age group of 10 to 18 years; neuroblastoma, retinoblastoma, and renal and hepatic tumors were seen commonly in the age group of 0 to 9 years. The most common presentation in leukemia was fever, while lymphadenopathy was the chief complaint in lymphoma. Local swelling and pain were the presenting symptoms in malignant bone tumors, while STS patients had painless swelling.Conclusion This study provides an overview of the burden and pattern of childhood malignancy for the state of Odisha and acts as a roadmap for the clinicians to conduct further research in the field of pediatric oncology.
Keywords: pediatric malignancy; Eastern India; childhood leukemia